A series of polycyclic aromatic hydrocarbon-substituted metal-free porphyrins: Substituent effect on two-photon absorption property. (July 2017) - Sheng, Ning; Gu, Bing; Ren, Boxiao; Zhang, Jing; Wang, Yingying; Wang, Jingxia; Sha, Jingquan
Abstract: The third-order nonlinear optical properties of a series of naphthyl, phenanthrenyl, and pyrenyl substituted porphyrins have been comparatively investigated by performing the femtosecond-pulsed Z-scan measurements. Due to the expanded π system, both pyrenly substituted porphyrin (1 ) and phenanthrenly substituted porphyrin (2 ) exhibit large two-photon absorption cross sections up to 4.26 × 10 4  GM for1 and 1.36 × 10 4  GM for2  at the wavelength of 800 nm. The pyrenly substituted porphyrin (1 ) has the most excellent two-photon absorption property because of the intramolecular energy transfer from the excited pyrene moiety to the porphyrin moiety in porphyrin1 . The results confirm that porphyrins conjugated with external π electronic systems can lead to the significant enhancement in the two-photon absorption cross-section values. This research provides a useful guideline to the design of efficient two-photon absorbing materials. Highlights: The third-order nonlinear optical properties of naphthyl, phenanthrenyl, and pyrenyl substituted porphyrins have been investigated. Both the pyrenly-substituted porphyrin and the phenanthrenly - substituted porphyrin exhibit large two-photon absorption cross sections. The pyrenly-substituted porphyrin has the most excellent 2PA property because of the intramolecular fluorescence energy transfer.